Social support received by students in Malang against suicidal ideation - Putri Athirah Salsabilah Herwanto; Rinto Wahyu Widodo (Jurnal Psikologi Tabularasa, 2025)
The purpose of this study was to determine the effect of social support on suicidal ideation in students in Malang. This research method uses a quantitative approach with the type of correlation, with the number of respondents of 100 respondents. The sampling method uses convenience sampling. The measurement tools used were the Multidimensional Scale of Perceived Social Support (a = 0,99) and the Revised-Suicidal Ideation Scale (a = 0,943). Data analysis techniques using simple linear regression. The results of the analysis on the data showed a regression coefficient of -0.528 (p = 0.000) < 0.05. Based on these results, it can be concluded that social support has an effect on suicidal ideation in students in Malang. This research can provide information that the social support obtained can determine the suicidal ideation that a person has. Therefore, social support from family, friends, and Partners is given to students so that suicidal ideation does not change to the next stage of suicide.